Characteristics and Stability of the Phosphoric Acid-tributyl Phosphate Emulsions - Yuqing Cao, Yang Jin (Science Faculty of Chiang Mai University, 2019)
For providing a theoretical basis for the study on the demulsification method and experimental simulation, it is necessary to study the effects of physical properties on the demulsification of phosphoric acid-tributyl phosphate emulsion system, and investigate the variations of these properties during the demulsification process. In this study, the initial drop size distribution and average droplet size of emulsions at different aqueous and oil phase compositions and phase ratio were measured. The variations of emulsion demulsification ratio, density and viscosity versus time were investigated. The results indicated that there was a corresponding relationship among these variations, and these variations might be attributed to the coalescence frequency of emulsion droplets and the initial properties of the emulsion. The properties of the equilibrated aqueous and oil phases after demulsification were also measured. Stability of this emulsion system was studied by microscope and macroscopic observations, which showed that the droplets sedimentation and coalescence led to the destabilization. A model associated with these properties and demulsification time was fitted by dimensional analysis and proposed. The results showed that the mathematical model fit well with the experimental data. This model is reliable to predict the demulsification time in different conditions of manufacturing emulsion.